دور معايير الحوكمة الجبائية في مكافحة التهرب الضريبي - عيدي, الطيب; بوشيخي, عائشة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة بشكل رئيسي إلى تسليط الضوء على الدور الذي تؤديه معايير الحوكمة الجبائية في مكافحة التهرب الضريبي والتقليل من أثره السلبي على مردودية التحصيل الضريبي إذ تعتبر الإيرادات الضريبية أهم مصدر لإيرادات الدولة و نظراً لغياب الامتثال الضريبي الشامل يعتبر التهرب الضريبي من أكبر التحديات التي تواجهها الإدارة الضريبية. و قد خلصت نتائج الدراسة إلى أن تطبيق معايير الحوكمة الجبائية يؤدي إلى إضفاء الثقة والمصداقية على القوائم المالية وعلى التصريحات المقدمة من طرف المكلفين و منه الحد من ظاهرة التهرب الضريبي. This study mainly aims to shed light on the role that tax governance standards play in combating tax evasion and reducing its negative impact on the cost-effectiveness of tax collection, as tax revenues are the most important source of state revenue, and given the absence of comprehensive tax compliance, tax evasion is one of the biggest challenges facing the Tax administration. The results of the study concluded that the application of tax governance standards leads to adding confidence and credibility to the financial statements and the statements made by the taxpayers, thus reducing the phenomenon of tax evasion.
The role of tax governance standards in combating tax evasion
مقال
Keywords: الحوكمة الجبائية, الإدارة الجبائية ,التهرب الضريبي, المجتمع الضريبي.; Tax governance, tax administration, tax evasion, tax society